1977
DOI: 10.1161/01.res.40.5.510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical training on end-diastolic volume and myocardial performance of isolated rat hearts.

Abstract: SUMMARY We studied the performance of ventricular muscle and cardiac function of hearts from rats conditioned by swimming (CH) and from sedentary rats (SH) in an isolated working heart apparatus modified to measure end-diastolic volume by dye dilution. Instantaneous aortic flow, left ventricular (LV) pressure and oxygen consumption were measured. Heart rate and mean aortic pressure were kept constant, and atrial filling pressure was varied from 5 to 20 cm H 2 O. Heart weights of SH and CH were equal and end-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
4

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 17 publications
3
30
4
Order By: Relevance
“…The effect of exercise on muscle mass in hypertension is controversial with various studies indicating both hypertrophy as a result of exercise (Barnard, et al 1980) and a reduction in hypertrophy (Hinderliter, et al 2002). There were others however, indicating no significant change in muscle mass due to exercise (Bersohn and Scheuer 1977). Our findings here tend to agree with the latter observation.…”
Section: Discussionsupporting
confidence: 82%
“…The effect of exercise on muscle mass in hypertension is controversial with various studies indicating both hypertrophy as a result of exercise (Barnard, et al 1980) and a reduction in hypertrophy (Hinderliter, et al 2002). There were others however, indicating no significant change in muscle mass due to exercise (Bersohn and Scheuer 1977). Our findings here tend to agree with the latter observation.…”
Section: Discussionsupporting
confidence: 82%
“…This ventricular pressure-function curve (32) is a valid index of left ventricular contractility if there is no change in left ventricular compliance. Physical training does not alter left ventricular compliance (33). Thus, the increase in the slope of the pressure-function curve (left ventricular function index in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…3) could be used to indicate that myocardial contractility increased in the dobutamine and exercise groups. Other investigators have shown that the mechanical performance of the heart is improved in physically conditioned animals (4,33,34), but the biochemical adaptation in cardiac muscle responsible 'for the increase in myocardial contractility has not been fully elucidated (1,24,35).…”
Section: Resultsmentioning
confidence: 99%
“…In the first series ofexperiments hearts were perfused for analysis of pump function, myocardial function, and cardiac metabolism. Full descriptions of the isolated working rat heart apparatus have been published previously (1 [1][2][3][4][5][6][7][8][9][10][11][12][13]. The Cardiac function was assessed at two levels of preload at each of three levels of afterload.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of this method and the validation for estimating ventricular volumes has been published previously (13). For (12).…”
Section: Methodsmentioning
confidence: 99%